Incidencia de las crisis familiares paranormativas en las relaciones de parejas, estudio de caso de las familias que asisten en el patronato municipal del cantón del Guabo, año 2013. - Bohórquez Lozada, Julia Isabel (2014)
The life cycle of the family, comprising several phases of training, extension, contraction and dissolution, emphasizing it as evolutionary, historical and psychological category, ie, we refer to events from this cycle by which every family travels as marriage, birth of children and entry of these institutions, guardianship termination, retirement, among others, and events that occur and the family unexpectedly surprised as accidents, the appearance of a problem such as physical or mental illness as well as consumption by some member of the family of psychotropic substances like drugs or alcohol, addiction to gambling or suicide attempts.